2002
DOI: 10.1081/jcmr-120003947
|View full text |Cite
|
Sign up to set email alerts
|

Fully Refocused Gradient Recalled Echo (FRGRE): Factors Affecting Flow and Motion Sensitivity in Cardiac MRI

Abstract: The Fully Refocused Gradient Recalled Echo (FRGRE) magnetic resonance pulse sequence, previously reported as True FISP, was implemented and reported on a GE Signa CV/i 1.5T scanner. The purpose of this research was to optimize the pulse sequence design and scanning parameters to improve image quality for cardiac applications. A 2-D, multi-slice, multi-phase, breathold, segmented k-space, prospectively gated FRGRE sequence was implemented with TE and TR values as short as 0.9 and 3.0 msec, respectively. Pulse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Primarily, they criticise the use of an echo time of 4.8 ms which results in so-called spin dephasing artefacts which display the transstenotic jet as a (gray to black) signal void which makes it difficult to reliably measure the aortic valve area. Moreover, Friedrich et al recommend the use of a steady-state free precession (SSFP) sequence with shorter echo times which is less susceptible to this problem [14] and thus more easily identifies the orifices. In a recent study, they have shown that MR imaging using a SSFP sequence reliably visualizes the area of the valvular orifice in symptomatic patients with aortic valve stenosis [15].…”
Section: Discussionmentioning
confidence: 98%
“…Primarily, they criticise the use of an echo time of 4.8 ms which results in so-called spin dephasing artefacts which display the transstenotic jet as a (gray to black) signal void which makes it difficult to reliably measure the aortic valve area. Moreover, Friedrich et al recommend the use of a steady-state free precession (SSFP) sequence with shorter echo times which is less susceptible to this problem [14] and thus more easily identifies the orifices. In a recent study, they have shown that MR imaging using a SSFP sequence reliably visualizes the area of the valvular orifice in symptomatic patients with aortic valve stenosis [15].…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, SSFP is generally the preferred sequence for assessing bioprostheses because of its superior signal-to-noise ratio, clear-cut bloodtissue contrast, and high spatial and temporal resolution, making the accurate identification of the fast-moving delicate valve cusps easier. 28,29 Schlosser et al 30 demonstrated that the assessment of aortic valve stenoses using SSFP correlates better with TEE compared with FGRE. However, when flow artifacts render SSFP images of nondiagnostic quality, we showed that the application of FGRE can improve image quality and allow image analysis in select cases.…”
Section: Challenges Of Cmr When Imaging Aortic Bioprosthesesmentioning
confidence: 99%
“…Another option would be to expand to a three-echo sequence and determine the velocity map as Nielsen and Nayak [23] did; however, this would require an even longer TR. The sensitivity to artifacts from through-plane flow might be reduced using a second bipolar gradient after the second readout to make the sequence flow compensated again [12,13]. The multiecho PC-SSFP sequence, as was described in this paper, might be better suitable for cerebrospinal fluid flow measurements in the brain, as velocities are lower, pulsatility is less and uniform surrounding tissue is present for phase offset measurement.…”
Section: Discussionmentioning
confidence: 94%
“…The uncompensated bipolar gradient and the long TR made the sequence sensitive to fast flowing and pulsatile blood [12,13]. To illustrate the effect of the uncompensated gradient, we additionally turned the velocity encoding gradient off.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation